PRODUCT AND SERVICE DIFFERENTIATION STRATEGIES IN MICRO COFFEE SHOP BUSINESSES: A QUALITATIVE CASE STUDY OF KOPI OMAHAN - Ikhrimah, Nada Mufidatan; Kamilati, Izzatun Nidail; Elisa Uswatun Hasanah; Fanesha Dea Abhista; Nicko Aji Purnomo; Mikhael Rafael Montoya; Fitra Rizqi Noveridho; Divani Adha Maharani; Amelia Setyawati (Nusantara Economics and Entrepreneurships Journals, 2025)
Micro, small, and medium enterprises (MSMEs) in the culinary sector, especially coffee shops, face increasingly high levels of competition as coffee consumption culture grows and similar businesses expand. These conditions require business actors to implement differentiation strategies that can create added value and competitive advantages. This study aims to analyze the product and service differentiation strategies implemented by Kopi Omahan as a local micro coffee shop business. The study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews with business owners, direct observation of operational activities and the atmosphere of the shop, and supporting documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that Kopi Omahan implements product differentiation through periodic menu innovation, the use of Indonesian coffee beans, manual brewing methods, and the creation of unique signature menus. Service differentiation is realized through a personalized customer experience, a vintage-style shop atmosphere, educational interactions between baristas and customers, and the implementation of a barcode-based ordering system to improve service efficiency. These differentiation strategies play an important role in building customer loyalty and maintaining business sustainability amid limited resources.